Translucent Mystery: A Case Report on Intraocular Lens Opacification - Gariyashee Lahkar; Kriti Bhatt; Meera Byju Rahim; Kamatchi Nagu; Madhu Shekhar (TNOA Journal of Ophthalmic Science and Research)
Intraocular lens (IOL) opacification, following cataract surgery, poses a significant challenge in the management and restoration of visual outcomes. We report a case of a 74-year-old female presenting with progressive vision loss due to total opacification of a previously implanted IOL. Surgical intervention included explantation of the opacified IOL and replacement with a 3-piece acrylic IOL. Post-operative assessment revealed significant visual improvement. This case highlights the need for further research into the underlying mechanisms of IOL opacification, the type of lens material that might predispose to such complications, and optimizing treatment strategies as well as outcomes in affected patients.